Estimation of the world beekeeping market - Malyshev, Victor; Lopukh, Liudmila; Yatsiv, Yuliia; Gab, Angelina; Shakhnin, Dmytro (Technology audit and production reserves, 2026)
The object of research is the world beekeeping market, the ecological role and physicochemical properties of the quality of honey and beekeeping products. The problem of generalizing and systematizing the results of research on the global beekeeping market is solved. It is determined that the key factors of market growth are the demand for organic and natural sweeteners in the food industry and beverage production, the excellent natural healing properties of honey and beekeeping products, and the environmental benefits of organic farming. It is shown that significant global challenges to market development are the reduction of the bee population due to the use of pesticides and the loss of habitat. It was determined that in 2024, the North American segment was the leader by geographical regions with a revenue share of 40.1%, by product type – the honey segment (88.2%), by application – the food and beverage segment (39.9%), by end user – the food industry segment (54.9%), by sales channels – the supermarket and hypermarket segment (34.7%), by funding distribution – the bee disease prevention segment (29.9%). It was determined that in 2023, the beehive segment dominated by equipment segments (48.1%), by geographical regions – the Asia-Pacific segment (33.1%). The physicochemical qualities of honey were studied. The mass fraction of water in the studied samples (Kyiv region, Zhytomyr region, Chernihiv region, Republic of Moldova) of honey ranged from 17.5% to 19.8%, diastase number – from 15.54 to 38.59 Gothe units, electrical conductivity – from 0.349 Ms/cm to 0.611 Ms/cm, reducing sugar content – from 78.56% to 80.7%, which meets quality standards. Generalization and systematization of data on the world beekeeping market and experimental determination of the physicochemical properties of honey and beekeeping products made it possible to obtain new data on the research topic for use in the beekeeping industry in Ukraine.